Jabatan Mufti Negeri Pahang e-Khutbah portal / Nor Zalina Ismail …[et al.] - Ismail, Nor Zalina; Muhamad, Noor Azila; Abd Aziz, Muhd. Eizan Shafiq; Razak, Mohd. Rizal (2014)
Khutbah is a sermon preached by an imam in a mosque on every Friday noon prayer. E-Khutbah is the system developed by UiTM Pahang Diploma in Computer Sciences practical student for Pejabat Mufti Negeri Pahang. Previously, khutbah is kept in Khutbah Section in physical file or folders. Once a month, imams in Pahang will collect the khutbah at Pejabat Mufti Negeri Pahang situated at Pekan, Pahang. First problem occurred with the previous khutbah storing and collecting process is time and cost consuming for imam to collect the khutbah. Another problem is the previous khutbah is difficult to retrieve by public for future references. This system uses the System Development Life Cycle that involves six processes. The processes are planning, analysis, design, implementation, testing and maintenance. Activity can be done by using e-Khutbah are uploading and downloading the khutbah, search the previous khutbah by month, year and the khutbah writer. e-Khutbah is a simple system but very beneficial to Khutbah Section in storing process and also helps the imams in collecting process as long the imams have the internet connection in their areas. Another benefit is easy for public to retrieve the previous khutbah for future used.